Sport policy formation and enactment in post-devolution Wales: 1999–2020. Issue 2 (3rd April 2022) - McInch, Alex; Fleming, Scott
ABSTRACT: Sport Wales (previously the Sports Council for Wales) is the lead non-government organisation for the delivery and management of sport policy in Wales and receives an annual grant from the Welsh Government, which is supplemented by additional money from the National Lottery. There are also 22 unitary authorities that are responsible for school and community-level sport and physical activity provision. The purpose of this article is to undertake a policy critique of sport in Wales since devolution. The provided commentary charts the development of Welsh sport policy since 1999 as part of an overall governmental emphasis on physical health and wellbeing. It is divided into the three organising themes that reflect three domains of sport and physical activity participation – school, community and elite. The analysis is predicated on a review of outcomes and impact on different sectors and draws upon (some) comparisons with the English context. The principal conclusion is that even though the Welsh Government has been led by the Labour Party since devolution, the adoption of neo-liberal principles has (at least implicitly) impacted negatively on policy formation and enactment. This article offers new insight into sports policy development and enactment in Wales since 1999 and draws attention, in particular, to the importance of sport and physical activity at a time of global pandemic as well as the neglect of black, Asian and minority ethnic groups in policy discourses.